Research on the Progress of Microbiological Parametres During the Maturation of Two Kinds of Semi-Hard Cheese - Mirela Jimborean; Dorin Tibulca (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology, 2014)
The microbiological analysis is being done since the moment of production until the end of maturation of two kinds of semi-hard cheese (Olanda and Moeciu). It was identified the total number of germs using the horizontal method for the list of micro-organisms; for the numbering of yeasts and moulds it was used the technique of countering at 25 degrees Celsius; for the detection of coli form bacteria was used the number’s method most probably at 30 degrees Celsius; to establish the number of Escherichia coli was used the technique of the probable number; for the numbering of the coagulum-positive staphylococcus the standard stipulates the numbering of the colonies obtained on a solid environment (the environment Baird-Baker), after the aerobic incubation  at 35 degrees Celsius or 37 degrees Celsius.